Determinants of social media risk attitude / Azitadoly Mohd Arifin … [et al.] - Mohd Arifin, Azitadoly; Mohamad Basir, Faziatul Amillia; Roslan, Azreen; Azhari, Nurfariza (Universiti Teknologi MARA, Selangor, 2018)
In the era of digital technology, with the advancement of technologies, social media has become an essential foundation for communications across multiple generations. According to the Malaysian Communication and Multimedia Commission report, in the year 2016, about 21.9 million out of the 31.7 million total population of Malaysia was classified as social users. The breakdown of the social users are 97.3% claiming to have their own Facebook account, 56.1% with their own Instagram account and 45.3% are YouTube users. The main objective of this paper is to examine the determinants of social media risk attitude in Kuala Selangor, comprises three independent factors which are entertainment, sociality and information. This study was conducted through questionnaires distributed to 100 individuals in the Kuala Selangor area and regression analysis was used to analyze the findings. The results showed that there was significant relationship between the entertainment factor and information factor towards the social media risk attitude. This indicates that the risk attitudes of social media in the Kuala Selangor area, is heavily influenced by the entertainment and information factors. The sociality factor however was insignificant towards the risk attitudes of the social media